Design of a Bispecific HIV Entry Inhibitor Targeting the Cell Receptor CD4 and Viral Fusion Protein Gp41 - Yan, Hongxia; Wu, Tong; Chen, Yue; Jin, Hongliang; Li, Li; Zhu, Yuanmei; Chong, Huihui; He, Yuxian (Frontiers in Cellular and Infection Microbiology, 2022)
Given the high variability and drug-resistance problem by HIV-1, development of bispecific or multi-specific inhibitors targeting different steps of HIV entry is highly appreciated. We previously generated a very potent short-peptide-based HIV fusion inhibitor 2P23. In this study, we designed and characterized a bifunctional inhibitor termed 2P23-iMab by genetically conjugating 2P23 to the single-chain variable fragment (scFv) of ibalizumab (iMab), a newly-approved antibody drug targeting the cell receptor CD4. As anticipated, 2P23-iMab could bind to the cell membrane through CD4 anchoring and inhibit HIV-1 infection as well as viral Env-mediated cell-cell fusion efficiently. When tested against a large panel of HIV-1 pseudoviruses with different subtypes and phenotypes, 2P23-iMab exhibited dramatically improved inhibitory activity than the parental inhibitors; and especially, it potently inhibited the viruses not being susceptible to iMab. Moreover, 2P23-iMab had a dramatically increased potency in inhibiting two panels of HIV-1 mutants that are resistant to T-20 or 2P23 and the infections of HIV-2 and simian immunodeficiency virus (SIV). In conclusion, our studies have provided new insights into the design of novel bispecific HIV entry inhibitors with highly potent and broad-spectrum antiviral activity.